New Religions and Youth Movements: Overlapping But Distinct Categories - Lewis, James R.; Ze’en, Zhou (International Journal for the Study of New Religions, 2021)
The present article delineates a distinction between New Religious Movements (NRMs) and a specific category of youth movement—which we will designate as Youth Identity Movements (YIM)—that is frequently, but not invariably, an NRM. We will argue that this distinction has been missed in large part because of the overlap between the participants in these two movements. We will further point out that, back in the Seventies when new religions emerged as significant social phenomena, it would have been difficult to have distinguished religiously-oriented Youth Identity Movements from other New Religious Movements. It is only now, with the benefit of hindsight and the ageing of NRM memberships, that such movements can be brought into focus.